Letramento social e cidadania : práticas de leitura para o 6º ano do ensino fundamental - Correia, Ingrid Kelly de Oliveira (2018)
This report aims at the presentation of a pedagogical book for Portuguese teachers which aims to promote social literacy using texts that encourage reflection and debate about discourses of citizenship and the multiple violences present in the school space, as well as to assist the development of students' communicative competence through the association between language, text and social context. The theoretical conceptions discussed here are based on the concept of discourse as the moment of social practices, Fairclough (2008); in literacy studies that understand it as social practices involving reading and writing and its consequences for society, Street (2003,2014); Kleiman (2008); Rojo (2009), as well as in reading and writing studies as discursive practices inseparable from the contexts in which they are developed, Kleiman (2008). The elaboration of the product had as research field an educational unit that is part of the public schools of Sergipe/Brazil, located in a peripheral district of the capital, and as target group, the 6th year of elementary school. This research fits the universe of educational action research, Tripp (2005), and collaborative research, the results obtained led to self-reflection of the teacher and students about education, about the social practices of that community and led to the planning of actions, from the practices of reading and writing, which will influence the daily life in and out of school.